Probiotics: A Study on Its Sources, Separation, Characterization, and Evaluation: Exploring the Use and Efficacy of Probiotics for Various Goods (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Probiotics, which are living cells with various beneficial qualities, have been widely investigates and economically used in a variety of goods across the globe. The use of genetic techniques to understand the functional functions of probiotics has increased as a result of this work, which looks at completely sequenced genomes. However, evidence from carefully performed clinical research may not essentially support the favorable benefits of probiotics.